A Secure Framework for Messaging on Android Devices with Honey Encryption (International Journal of Engineering and Computer Science, 2017)
Nowadays, there are various encryption techniques used to secure the messaging services before send it through the unsecure network. But still the attackers hack the message by using various hacking methods. So for providing more security and to avoid the Brute force type attack, we provide a best encryption technique with encoding scheme. The proposed approach aim to develop a secure messaging framework for Android based devices using Honey Encryption with Symmetric key cryptography techniques, for preventing the text based messages from brute face attacks in order to make messaging communication more secure and efficient. In this work we combine the Honey encoding with both AES and Blowfish separately and then compare the performance of both the algorithm. Experiments show that Blowfish algorithm when combined with Honey Encryption scheme produces result in less time.